(untitled) (Comprehensive Journal of Science, 2025)
The present study aims at: (1) investigating the effect of applying teaching skills (pedagogical methodologies and teaching aids) on the overall performance of instruction, and (2) evaluating the employment conditions that probably influence the teacher’s attitude towards applying teaching skills in pedagogical practices. To achieve these objectives, the designed methodology adopted a questionnaire-based survey of 35 faculty members employed in Faculty of Management and Finance. The sample represented 25% of the total number of teachers working for this faculty. The results showed that faculty member’s possession of teaching skills (pedagogical methodologies and teaching aids) had direct relationship with his/her instruction performance, and that the employment variable of "type of contracting (part/full-time-based)" has the main influence, at 5% significance level, on the one’s attitude towards applying teaching skills. In addition, full-time faculty members exhibited greater willingness towards learning and applying teaching skills compared with their part-time counterparts. The study concluded that teacher training and development as well as ensuring quality standards in education should be emphasized more in future in the Libyan higher education system. As teacher form an important input in education sector, the study recommends to consider a serious national plan for teacher training and development in order to improve the education quality in Libya..